Biochemical evaluation and molecular docking assessment of the anti-inflammatory potential of Phyllanthus nivosus leaf against ulcerative colitis. Issue 5 (May 2020) - Johnson, Titilayo Omolara; Odoh, Kenneth Daniel; Nwonuma, Charles Obiora; Akinsanmi, Augustina Oduje; Adegboyega, Abayomi Emmanuel
Abstract: Ulcerative colitis (UC) is an inflammation of the colon that can progress to colorectal cancer if left untreated. No medication completely cures UC and natural products are sources of alternative approaches. This study aimed to determine the anti-inflammatory potential of Phyllanthus nivosus leaf extract and fractions in a rat model of ulcerative colitis and to identify the active ingredients. UC was induced in rats by intra-rectal infusion of 1ml of 4% acetic acid (AA) in normal saline. AA exposed groups of rats were treated with 100 mg/kg bodyweight of methanol extract, hexane, ethyl-acetate and butanol fractions orally for four days. Another group received the standard drug - Dexamethasone and control rats were given distilled water only. Some biochemical changes were evaluated and the active ingredients were identified using Gas Chromatography-Mass Spectrometry (GC-MS) followed by molecular docking against interleukin-1-beta converting enzyme (Caspase-1), beta-2 adrenergic receptor (ADRB2), cyclooxygenase-2 (COX-2) and tumour necrosis factor-alpha (TNF-α). Exposure of rat colon to acetic acid significantly altered (p < 0.05) serum levels of tumour necrosis factor-alpha (TNF-α), interleukin – 6 (IL-6), nitric oxide (NO), lipid peroxidation product (malondialdehyde or MDA), reduced glutathione (GSH); and activities of superoxide dismutase (SOD) and catalase (CAT). These alterations were however restored in the rats treated with P. nivosus leaf with the ethyl-acetate fraction displaying the highest ameliorative activity. GC-MS analysis of the ethyl acetate fraction revealed the presence of 40 compounds which when subjected to molecular docking demonstrated varying degrees of binding affinities for the protein targets. Ethyl iso-allocholate demonstrated the highest binding affinity for caspase-1, cholest-22-ene-21-ol, 3, 5-dehydro-6- methoxy-, pivalate for ADRB2 and TNF-α; and alpha-cadinol for COX-2. The anti-inflammatory potential of Phyllanthus nivosus leaf as a natural remedy and as a source of new drugs against ulcerative colitis is validated. Abstract : Ulcerative colitis; Tumor necrosis factor-α; Caspase-1; beta-2 adrenergic receptor; cyclooxygenase-2; ethyl iso-allocholate; isoledene; alpha-cadinol; Phyllanthus nivosus ; Molecular Docking; Chemistry; Biological Sciences; Biochemistry; Pharmacology